The Role of Artificial Intelligence in Enhancing Human Longevity: Mitigating Cognitive Overload for Extended Lifespan Among Master's Students in Mathematics at the Catholic University of Ghana - Addae, Richmond Kakra; Brown, Cecilia (Manunggal Halim Jaya, 2025)
This article studied the influence of artificial intelligence on alleviating cognitive load and promoting cognitive longevity in master's mathematics students at the Catholic University of Ghana. Stress in academic programs, time constraints, and burnout are rising issues, particularly in postgraduate programs in STEM. Therefore, this study examines the impact of AI apps such as ChatGPT, WolframAlpha, and Grammarly on providing cognitive support and emotional sustenance in academic environments. The study is guided by Cognitive Load Theory (Sweller, 1988), Allostatic Load Theory (McEwen, 1998), and Socio-Technical Systems Theory (Trist, 1981) and follows a mixed-method approach consisting of survey data from 100 master's students and in-depth interviews. The survey revealed that 78 percent were moderately to highly cognitively overloaded, while 65 percent utilized AI to work on their academic tasks. A notable negative relationship was found between AI use and perceived stress (r = -0.42, p < 0.01), with more confidence in academic work and improved time management. ANOVA revealed significant differences in stress levels among the different frequencies of AI use (F = 4.56, p < 0.05). Qualitative analyses generated the core themes of